Circadian rhythm disruption in critically ill patients. (31st March 2023) - Felten, Matthias; Dame, Christof; Lachmann, Gunnar; Spies, Claudia; Rubarth, Kerstin; Balzer, Felix; Kramer, Achim; Witzenrath, Martin
Abstract: Patients admitted to the intensive care unit (ICU) are in need of continuous organ replacement strategies and specialized care, for example because of neurological dysfunction, cardio‐pulmonary instability, liver or kidney failure, trauma, hemorrhagic or septic shock or even preterm birth. The 24‐h nursing and care interventions provided to critically ill patients significantly limit resting and/or recovery phases. Consecutively, the patient's endogenous circadian rhythms are misaligned and disrupted, which in turn may interfere with their critical condition. A more thorough understanding of the complex interactions of circadian effectors and tissue‐specific molecular clocks could therefore serve as potential means for enhancing personalized treatment in critically ill patients, conceivably restoring their circadian network and thus accelerating their physical and neurocognitive recovery. This review addresses the overarching issue of how circadian rhythms are affected and disturbed in critically ill newborns and adults in the ICU, and whether the conflicting external or environmental cues in the ICU environment further promote disruption and thus severity of illness. We direct special attention to the influence of cell‐type specific molecular clocks on with severity of organ dysfunctions such as severity of brain dysfunction, pneumonia‐ or ventilator‐associated lung inflammation, cardiovascular instability, liver and kidney failure, trauma, and septic shock. Finally, we address the potential of circadian rhythm stabilization to enhance and accelerate clinical recovery.